2021
DOI: 10.1089/lgbt.2020.0178
|View full text |Cite
|
Sign up to set email alerts
|

The Health and Well-Being of Transgender Australians: A National Community Survey

Abstract: Purpose: Transgender, including gender diverse and nonbinary (trans), people experience significant health disparities. We aimed to better understand the health status and needs of Australian trans people to guide resources and health and well-being programs. Methods: This anonymous, cross-sectional online survey utilized nonprobability snowball sampling of Australian adults (18 years and over) who self-identified as trans between September 2017 and January 2018. This descriptive study assessed demographic dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
79
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(103 citation statements)
references
References 19 publications
7
79
2
Order By: Relevance
“…This is considerably higher than recent Australian population data highlighting a smoking prevalence of 16.9% in the general population in persons aged 45-54 years (males 19.3%, females 14.7%) (24). Smoking rates in trans individuals aged ≥45 in our study were also higher than a recent cross-sectional survey of Australian trans adults (current smoking 15%), noting that this survey reflected a younger demographic with a median age of 28 years (25).…”
Section: Cardiovascular Risk Factors In Transgender Individuals Receiving Feminizing Hormone Therapy Compared To the General Australian Pcontrasting
confidence: 67%
“…This is considerably higher than recent Australian population data highlighting a smoking prevalence of 16.9% in the general population in persons aged 45-54 years (males 19.3%, females 14.7%) (24). Smoking rates in trans individuals aged ≥45 in our study were also higher than a recent cross-sectional survey of Australian trans adults (current smoking 15%), noting that this survey reflected a younger demographic with a median age of 28 years (25).…”
Section: Cardiovascular Risk Factors In Transgender Individuals Receiving Feminizing Hormone Therapy Compared To the General Australian Pcontrasting
confidence: 67%
“…Transgender individuals (trans) experience a gender identity (which may be binary or non-binary) different from that which they were presumed at birth, and often, but not always, this gender incongruency is associated with significant psychological distress, known as gender dysphoria ( 1 , 2 ). Despite considerable progress made by the trans community over the past decade in regard to visibility and acceptance, trans people still face significant obstacles and prejudice ( 3 , 4 ), social stigma and discrimination, leading to job and housing insecurity, verbal and physical violence, and barriers to accessing appropriate healthcare ( 3 ). Similarly, trans people experience alarmingly high rates of mental health disorders compared to the general population ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, trans people experience alarmingly high rates of mental health disorders compared to the general population ( 5 , 6 ). A recent study looking at self-reported mental health diagnoses within the trans community has indicated that 73% of trans adults have been diagnosed with depression in their lifetime, 67% have been diagnosed with anxiety, and 43% attempted suicide in their lifetime ( 3 ). In contrast, self-reported rates of depression, anxiety and suicide attempts for the general population are indicated at 11.6%, 26.3%, and 3.2% respectively ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Employees at work alienate themselves from transgender coworkers due to their personal characteristics [39]. Their personal attributes seem strange as these attributes do not align with either male or female attributes [40][41][42]. Employees maintain a distance as a result of the lack of the proper identity of transgender people and coworkers sometimes feel deficient in finding a suitable name or pronoun to address their transgender coworkers [39,40].…”
Section: Literature Reviewmentioning
confidence: 99%